Walkability and property values in Omaha, NE - Stachon, Greg (Kansas State University, 2018)
Recent studies have shown that walkability can have a positive impact on a community. Walkability has been associated with better public health (Jensen et al., 2017), lower carbon emissions (Morris, 2009), more taxes per land area, and more transportation options which helps low income residents (Speck, 2012; Forsyth, 2015). Additionally, there have been studies done that show housing in walkable areas commands a price premium (Pivo & Fisher, 2011). This should be a good sign for communities because walkable areas are more likely to get built if a land developer can fetch a higher price for a walkable property. But what exactly is the walkability premium for properties in Omaha, NE if there is one? The studies that have linked walkability to higher property values were done in larger cities and few studies have looked at smaller metros in the Midwest (Hack, 2013; Leinberger & Alfonzo, 2012). This study seeks help to fill in this gap in the research by looking specifically at walkability’s correlation to property values in Omaha, NE, a mid-size midwestern city. This study looked at three different land uses in Omaha, NE to see if there is a correlation between walkability and property value. The three land uses were single-family houses, apartments, and restaurants. Property values were measured using data from the Douglas County, NE assessor’s office. The walkability of each parcel was measured using a 1-100 scale as generated from WalkScore.com. A positive correlation between WalkScore and property values was found but only in the eastern part of the city. The correlation was highest in the apartment land use and lower but still positive for single-family houses and restaurants. In the western part of Omaha, there were negative correlations between WalkScore and property value across all three land uses. These results are expected to contribute to walkability literature as a case study on the relationship of walkability to property valuation. It could also be used by municipalities and land developers who are interested in the value of properties they are developing for their communities.
Keywords: Walkability; Property value; Omaha; Nebraska; WalkScore